Chopin kopiujący Chopina - Rink, John (Studia Chopinowskie, 2018)
This paper investigates a number of pertinent issues surrounding the copies that Chopin prepared of his own music. His propensity for making compositional changes at subsequent stages in a work’s evolution is of course well known and much documented, but his skills as a copyist – defined in terms of notational clarity, fidelity to the original source, appropriate improvements to presentation and so on – have received little comment in the literature. Close study of the two surviving autograph manuscripts of one of Chopin’s late works, the Barcarolle Op. 60, reveals not only changes of compositional substance but also indications of an inattentiveness which almost certainly prevailed when Chopin copied out the manuscripts of other pieces. Comparison with relevant first editions also helps to challenge any assumptions we might have about the unqualified authority of Chopin’s autograph sources.